Serum Electrolyte Levels in Children with Febrile Seizures: A Cross-sectional Study - Ray, Sampurna; Halder, Dipanjan; Karar, Neha; Biswas, Prativa; Hayder, Shah Masud; Mondal, Anwesha; Sardar, Tapas; Kammar, Chandramohan S (Journal of clinical and diagnostic research, 2025)
Introduction: Febrile seizures are the most common type of childhood seizure, typically occurring in children younger than 60 months of age. They are categorised into simple and complex febrile seizures. The recurrence of febrile seizures is also high. Among the various known risk factors for recurrence, serum sodium is a quantifiable and correctable factor. However, there are very few studies in this field to determine whether other serum electrolytes at presentation also have any association with the type of seizure or the patient’s gender, which are non modifiable risk factors for recurrence. Aim: To measure serum electrolyte levels (sodium, potassium, calcium, magnesium) in patients with febrile seizures at presentation and to find out its association with the type of seizure and the patient’s sex. Materials and Methods: This cross-sectional study was performed on 76 patients aged six months to five years who were admitted to the Paediatrics Inpatient Department (PIPD), attended the Paediatrics Out-Patients Department (POPD) and visited the Paediatrics Emergency of RG Kar Medical College and Hospital, Kolkata, West Bengal, India, with any episode of febrile seizure between April 2021 and March 2022. The serum electrolyte levels (sodium, potassium, calcium, magnesium) in patients with febrile seizures were measured. Data were analysed using STATA version 16 software, employing Fisher’s exact test, with a p-value of <0.05 considered statistically significant. Results: Out of the 76 study subjects, 55.26% were male and 44.74% were female, resulting in a male-to-female ratio of 1.23:1. Of the subjects, 93.42% had simple febrile seizures, while 6.58% exhibited complex febrile seizures. A statistically significant association was found between the type of febrile seizure and serum magnesium (p-value=0.006), as well as between the sex of the patients and serum calcium levels (p-value=0.012). No statistically significant association was observed between the sex of the study subjects and serum sodium (p-value=0.105), serum potassium (p-value=0.576), or serum magnesium levels (p-value=0.312). Furthermore, the type of febrile seizure showed no statistical significance with serum sodium (p-value=0.284), potassium (p-value=0.820), or calcium levels (p-value=0.373). Conclusion: The present study concluded a significant association between serum magnesium levels and the type of febrile seizure, as well as between serum calcium levels and the sex of the patients. Thus, measuring serum electrolytes in patients with febrile seizures at the time of presentation is beneficial, as it is easy to perform, provides rapid results and identifies correctable and quantifiable issues.